Impact of land use and seasonal variations on soil ecosystem under arid environmental conditions - Ullah, Rehmat; Khan, Khalid Saif Ullah; Mehdi, Shehzada Munawar; Nadeem, Ahmad; Habiab, Fareeha; Noor, Sobia; Iqbal, Muhammad (Journal of Pure and Applied Agriculture, 2023)
The experiments were carried out to evaluate dynamic trend of soil microbes in various seasons on existing cropping patterns on sloppy arable lands of Kahuta area. For this purpose, a series of experiments were initiated to monitor the soil biological status under wheatmaize and wheat-mungbean cropping patterns. From both patterns, soil samples were taken in summer, winter, spring and autumn seasons. The results differed significantly for soil microbial biomass carbon (SMBC), soil microbial biomass nitrogen (SMBN), soil microbial biomass phosphorus (SMBP) in all seasons under wheat-maize and wheat-mungbean cropping patterns. Similarly, soil enzymes, particularly soil dehydrogenase (SDH) and soil alkaline phosphatase (SAP) activated heterogeneously in these sites throughout the year and had a significant